Democratic Transitions in the Muslim World. Edited by Ali Salman, Mohammad Hashim Kamali and Mohamed Azam Mohamed Adil. Selangor, Malaysia: Pelanduk Publications - Syaza Farhan binti Mohammad Shukri (IIUM Journal of Religion and Civilisational Studies, 2020)
This is a Book Review